Konsep Kepemimpinan Profetik Dalam Membangun Sumber Daya Manusia Berbasis Islam Di Perpustakaan - Machsun Rifaudin (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2017)
Library need a leader who has high integrity to develop library along current times. One leadership style that can be applied in library is prophetic leadership. This research aims to explain about concept of prophetic leadership in management of human resources in library by study of literature method. Prophetic leadership appropriate and can applied in library because a leader who has a prophetic leadership style has a high integrity (As Sidq), reliable (Al Amanah) means the leader of library forms should prove a real job, At-Talbligh mean the leader of the library must be willing to receive constructive feedback, and Al Fatanah, leader of the library should make him able to work intelligently and decisively by combining intellectual intelligence (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ). Library leaders which good quality will deliver high quality human resources, therefore the role of head library in management of human resources is crucial to realize the human resources professional and competent in the library.